Hamzah Fanshuri tentang Konsep Wujud - Damanhuri Damanhuri (Jurnal Pemikiran Islam, 2021)
The purpose of this research is to explain about Sufism formulated by Sheikh Hamzah Fanshuri. He is quite famous in the 16th century AD Although the concept of Sufism Hamzah Fansuri already very old, but until now, this teaching is still studied in Aceh and in several other regions in Indonesia. Among the concepts of Hamzah Fansuri's Sufism that are still studied by many people is about the concept of existence. In the opinion of Sheikh Hamzah Fansuri, the essence of existence is one, namely the existence of God. Apart from the existence of God everything is not a real existence, but a reflection of the real existence. While this form is a relationship beamong matter, nature, asthma and af'al Allah. Regarding the existence of human beings, Sheikh Hamzah Fansuri  explained that human beings are the lowest form, even so,  they still have the opportunity to rise to a higher dignity.